Gluttony & Drunkenness in Ancient Israel - Welton, Rebekah (The Biblical archaeology review, 2020)
In Deuteronomy 21:18-21, a delinquent son is sentenced to death for being rebellious, as well as a glutton and drunkard. A close look at the foodways of ancient Israel suggests a better interpretation for the son’s crime.